Functional Disability on Instrumental/Activities of Daily Livings among Rural Older People in Nepal - Chalise, Hom Nath; Khanal, Binita (Journal of Karnali Academy of Health Sciences, 2020)
Background: Functional disability among older people is a growing concern for research for the quality of life of older people these days. The purpose of this paper is to present the situation of functional disability among Nepali older people living in a rural area. Methods: This is a cross-sectional study carried out in a rural area of Nepal. The total sample size for this study was 150 older persons 65 years and older. Functional disability on older people was assessed using internationally widely used instruments Activities of Daily Livings (ADLs) and Instrumental Activities of Daily Livings (IADLs). Results: Mean age of the care recipients (elderly) was 78.46 (±7.78) years. This study found a functional limitation on at least one ADL and IADL was 30% and 52%, respectively. Among the six items of ADLs highest problem was in incontinence (24%), followed by bathing (16%), use of toilet (14%), transfer within the home (10%), dressing and undressing (10%), and feeding (8%). Among IADLs highest dependency was in taking medicine (46%) followed by traveling (44%), shopping (40%), housekeeping (38%), and food preparation (34%). Conclusion: This study shows the functional limitations of Nepalese older persons living in the countryside are very high. ADLs and IADLs difficulties often correspond to the exact need for help, supervision, and hands-on care of an older person. The government should focus on some intervention programs for the wellbeing of older adults.